Early Experience With Pembrolizumab in Bacillus Calmette-Guérin Unresponsive Non–Muscle-Invasive Bladder Cancer - Chung Un Lee; Wan Song; Minyong Kang; Hyun Hwan Sung; Hwang Gyun Jeon; Seong Il Seo; Seong Soo Jeon; Se Hoon Park; Byong Chang Jeong (Journal of Urologic Oncology, 2023)
Purpose Radical cystectomy (RC) is recommended for patients with non–muscle-invasive bladder cancer (NMIBC) who are unresponsive to intravesical bacillus Calmette-Guérin (BCG) instillation. However, RC is a very risky treatment, and some patients cannot undergo RC due to old age, patient preference, and comorbidities. In this study, we investigated the efficacy of pembrolizumab, a programmed cell death protein 1 inhibitor, in patients with NMIBC unresponsive to intravesical BCG instillation. Materials and Methods Between December 2016 and February 2023, 24 patients who experienced recurrence after BCG treatment and subsequently received pembrolizumab were enrolled. We evaluated the patients’ response to pembrolizumab therapy using urine cytology, cystoscopic examination (with/without biopsy), and/or computed tomography imaging. The primary endpoint was the complete response (CR) rate 3 months after the first dose of pembrolizumab. Patients were followed up every 3 months for the first 2 years and every 6 months thereafter. Kaplan-Meier survival analysis was used to illustrate CR and the individual treatment course was demonstrated. Results The median follow-up period was 16 months (range, 2–68 months) and the median number of pembrolizumab administrations was 5 times (range, 3–39 times). Thirteen of the 18 patients (54.2%) with BCG-unresponsive NMIBC achieved CR at 3 months. The median duration of CR maintenance was 15 months (range, 5–47 months). Five patients (20.8%) showed no recurrence for 12 months after pembrolizumab administration. Seven patients underwent RC, and pathological reports showed T2 stage in 3 patients. To date, 1 patient (4.2%) has died. Conclusions Our early experience with pembrolizumab treatment for BCG-unresponsive NMIBC showed better results than those of the KEYNOTE-057 trial, which reported a CR rate of 40% at 3 months. However, long-term data and more cases are required to establish pembrolizumab therapy in patients with BCG-unresponsive NMIBC in a real-world setting.